COMPARING TOOLS PROVIDED BY PYTHON AND R FOR EXPLORATORY DATA ANALYSIS - Mahathir Rahmany; Abdullah Mohd Zin; Elankovan A Sundararajan (IJISCS (International Journal of Information System and Computer Science), 2020)
To uncover the insight behind the data, a comprehensive analysis is needed. Exploratory Data Analysis (EDA) is one of practical data analysis that will guide how to reveal any hidden information in the data. By doing EDA, any pattern and issue in the data will be seen and eventually will lead the hypothesis. To do EDA, besides any basic statistic is needed, a good tool to simplify the analysis is also a consideration. Python and R as a famous programming language in the data science world provide methods to implement that analysis. This paper will show how to perform EDA by utilizing Python and R programming.